Experimental study on cutting flexible sheet materials using an oscillating knife. Issue 3 (5th June 2017) - Cosson-Coche, Quentin; Cahuc, Olivier; Darnis, Philippe; Laheurte, Raynald; Teissandier, Denis; Chabirand, Didier
Abstract : Purpose: The purpose of this paper is to understand the impact of the cutting forces on the quality of pieces in industrial cutting of multi-ply textile material. It also tries to establish a cutting model that can simulate the cutting forces in order to understand the behaviour of the blade. Design/methodology/approach: Working on an industrial machine, a cutting head with an oscillating knife is instrumented with different sensors. Using this equipment, cutting forces can be analysed experimentally while the fabric is being cut along a straight line. Findings: A model of the physical phenomena of the cutting forces is proposed, taking different parameters into account such as the geometry of the blade, the properties of the material being cut and the parameters of the cut. The simulated forces and the monitored forces are compared and parameters for minimising the cutting forces of fabrics are deduced. Research limitations/implications: Due to the wide diversity of fabrics, all with different mechanical characteristics, this research only began with the study of denim in a straight cut. Originality/value: This paper describes an instrumentation of automatic cutting head for textile. It manages to simulate the action of the fabrics on the blade through effort monitoring and help in the understanding of the multi-ply cutting process.